Usefulness of Leifson Staining Method in Diagnosis of Helicobacter pylori Infection - Piccolomini, Raffaele (American Society for Microbiology, 1999)
The Leifson staining method was used to diagnose Helicobacter pylori infection and was compared to histology, culture, and the rapid urease test (RUT). Histology gave the best sensitivity (98%), compared to Leifson staining (97%), culture (92%), and RUT (85%) (P < 0.005). Leifson staining is a sensitive, rapid, economical method for diagnosis of H. pylori infection in dyspeptic patients.